Perbandingan Optimasi Kontroler Putaran Motor Permanent Magnet Syschronous Machine - Machrus Ali; Miftachul Ulum (Jurnal FORTECH, 2020)
Low torque low owned by PMSM (Permanent Magnet Synchronous Machine) required an excellent control model. PMSM uses the principle of faraday's law by rotating magnets in the coil by using other energy sources. When a magnet moves in a coil or vice versa. The engine rotation will change the magnetic force flux on the coil and penetrate perpendicularly to the coil so that a potential difference arises between the ends of the coil. The potential difference is caused by changes in magnetic flux. in order to get the best control method, a good speed control model is needed. In this study comparing PMSM speed control using PID, Fuzzy Logic Controller (LFC), and Adaptive Neuro-Fuzzy Inference System (ANFIS). The simulation results show that the best model on the ANFIS controller that is closest to Speed ​​Reff (300 rpm) is that ANFIS obtains the rotational profile with the smallest undershot, the fastest steady state, the best output current profile, the best torque profile, and the best voltage profile. The results of this study will be followed by the use of other Artificial Intelligence.